Second language learning motivation, life-long learning and 21st century skills in today’s globalized world: A validation study - Fajt, Balázs; Bánhegyi, Mátyás (Working Papers in Language Pedagogy, 2024)
Knowledge production in today’s world presupposes skills necessary for successful knowledge construction and knowledge update. Such skills include English as a foreign language (EFL), life-long learning and 21st century skills. This study presents a quantitative pilot study (N=200) that examines the relationship between EFL learning motivation, communication in L1 and L2, some aspects of life-long learning and certain 21st century skills. The paper seeks to explore what this relationship is like and in what way these factors are connected and how they potentially impact one another. The study presents the validation of the instrument used for the research, and reports some of the preliminary findings. Based on the results, it is concluded that the ideal L2 self is a predictor of L2 learning motivation, willingness to use dictionaries and cooperation during EFL classes. The results also indicate that participants exhibit the necessary ICT and L1 skills for their studies of EFL, and positively relate to communicative situations with native and non-native speakers of English.